Effects of reminiscence therapy on quality of life and life satisfaction of the elderly in the community: a systematic review - Eunyoung Shin; Myeongshin Kim; Seyoon Kim; Sohyune Sok (BMC Geriatrics, 2023)
Abstract Background Reminiscence therapy is known as an effective intervention method for elderly with various health conditions. This study was to provide basic data for contributing to the spread and development of effective intervention by analyzing the characteristics and effects of reminiscence therapy applied to the elderly at home. Methods To select the article to be studied, literature published from January 2000 to January 2021 was searched through eight databases. A total of 897 articles were searched, and the collected papers were analyzed using the flow chart of Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA). Of these, 6 articles suitable for the selection criteria were selected by reviewing titles and abstracts, excluding duplicate papers, using EndNote X9 and Excel 2013. The quality of literature was evaluated using the critical appraisal checklist of the Joanna Briggs Institute. Results For the characteristics of the selected literature, most of the literature published within the last 10 years was conducted, and the research design was conducted only in experimental research. The most common form of reminiscence therapy was group reminiscence, and the type was ‘simple reminiscence’. The intervention method of reminiscence therapy was provided in various ways, but ‘Sharing’ was mainly used, and the representative topic of recall was ‘Hometown’. Most of the intervention was performed less than 10 times and took about 60 min. Conclusion According to the results of this study, reminiscence therapy provided to the elderly living in the community was effective in improving their quality of life and life satisfaction. Therefore, it is suggested that reminiscence therapy can be an intervention method that is helpful for positive psychological factors and health promotion by improving the quality of life and life satisfaction of the elderly living in the community, and further, it is considered that the elderly can contribute to non-pharmacologically healthy aging in the community.